The Impact of Thematic Learning using Index Card Match Instructional Model on Students’ Conceptual Understanding - Hendawati, Yuyu; Sumiati, Tati; Pratomo, Suko; Nuraeni, Fitri; Susilawati, Yanti (International Conference on Elementary Education, 2020)
This study aims to investigate the effect of thematic learning using Index Card Match instructional model on students’ conceptual understanding. The method used in this study is Classroom Action Research involving fifth grade students in one of public primary school in Subang. Results suggest that after the implementation of thematic learning using Index Card Match instructional model, students’ conceptual understanding was improved. Additionally, data analysis imply that students’ learning activities throughout the three cycle of thematic learning with Index Card Match was increased at each meeting